Graphene lead oxide powder composite material and preparation method and application thereof

By reacting graphite powder, lead nitrate and ammonium nitrate at 400-500°C, the problem of complex and high cost in the preparation of existing graphene lead oxide powder composite materials is solved, and the low-cost and efficient preparation of graphene-rich composite materials is achieved, and the performance is improved.

CN119695143APending Publication Date: 2025-03-25CHAOWEI POWER GROUP CO LTD

Patent Information

Application Number
CN202411962255.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing graphene lead oxide composite materials are made in complex methods, with high cost, low purity, low conversion rate to graphite and poor performance.

Method used

Graphite powder, lead nitrate and ammonium nitrate were used to react at 400-500°C for 2-4 hours, the reaction gas was recovered and treated and ground to obtain a graphene lead oxide powder composite material. This method requires only one step of reaction, eliminating the use of expensive graphene and cumbersome intermediate operations.

Benefits of technology

It has achieved low-cost and efficient preparation of graphene lead oxide composite materials, with a carbon content of 18-28%, a purity of 80-90%, and a conversion rate of graphite to graphene of 80-90%, and a significant improvement in performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695143A_ABST
    Figure CN119695143A_ABST
Patent Text Reader

Abstract

The invention relates to a graphene lead oxide powder composite material as well as a preparation method and application thereof, belongs to the technical field of composite materials, and aims at solving at least one of the problems of complex preparation method, high cost, low purity, low graphite-to-graphene conversion rate, poor performance and the like of the existing graphene lead oxide powder composite material. The preparation method of the graphene and lead oxide powder composite material comprises the steps that graphite powder, lead nitrate and ammonium nitrate react for 2-4 h at the temperature of 400-500 DEG C, gas generated in the reaction is recycled, solids obtained in the reaction are ground, and the graphene and lead oxide powder composite material is obtained. The graphene and lead oxide powder composite material can be obtained only through one-step reaction, only graphite powder needs to be adopted as a raw material, expensive graphene does not need to be used, the production process is simple, any intermediate operation is not needed, the carbon content of the graphene and lead oxide powder composite material prepared through the method is 18-28%, the purity is 80-90%, and the graphene and lead oxide powder composite material is suitable for industrial production. And the conversion rate from graphite to graphene is 80-90%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a graphene lead oxide powder composite material and a preparation method and application thereof. Background Art

[0002] Graphite, graphene, activated carbon and other carbon materials are often used as additives for the negative active material of lead-acid batteries, which can significantly improve the capacity and cycle life of the battery. The conventional method is to add graphene and other carbon materials as additives during the mixing of the paste, but due to the low density of graphene, this method has poor mixing uniformity, which can easily cause graphene to agglomerate and disperse unevenly in the lead paste, affecting battery performance.

[0003] Patent CN117174900A discloses a lead-graphene negative electrode lead paste and a preparation method thereof. The method prepares graphene-containing lead powder according to a conventional ball milling process. Although the method can ensure the uniformity of graphene dispersion, the process is too complicated and the cost of preparing the lead-graphene composite material is relatively high.

[0004] Patent CN102881866A discloses a lead-carbon battery negative plate containing a lead-graphene composite material. The method uses an electrodeposition method to prepare the lead-graphene composite material, and then adds it with lead powder in proportion. The method requires the use of graphene materials during preparation, and it is compounded with lead by electrodeposition. The process is cumbersome and the cost is high. Summary of the invention

[0005] In view of the above analysis, the present invention aims to provide a graphene lead oxide powder composite material and a preparation method and application thereof, so as to solve at least one of the problems of the existing graphene lead oxide powder composite material preparation method being complex, high cost, low purity, low graphite to graphene conversion rate, poor performance, etc.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] In a first aspect, the present invention provides a method for preparing a graphene lead oxide powder composite material, comprising reacting graphite powder, lead nitrate and ammonium nitrate at a temperature of 400-500°C for 2-4 hours, wherein the gas generated by the reaction is recovered and processed, and the solid obtained by the reaction is ground to obtain the graphene lead oxide powder composite material.

[0008] Furthermore, the mass ratio of graphite powder, lead nitrate and ammonium nitrate is 0.1-0.4:1:0.3-0.5.

[0009] Furthermore, the method further comprises adding an organic swelling agent to carry out the reaction.

[0010] Furthermore, the organic swelling agent is ethanol or isopropanol.

[0011] Furthermore, the mass ratio of the organic expander to the graphite powder is 0.05-2:1.

[0012] Furthermore, the gas includes nitrogen dioxide.

[0013] Furthermore, the grinding is performed to a particle size of less than 5 microns.

[0014] In a second aspect, the present invention provides a graphene lead oxide powder composite material prepared by the above method, wherein the graphene lead oxide powder composite material has a carbon content of 18-28%, a purity of 80-90%, and a conversion rate of graphite to graphene of 80-90%.

[0015] In a third aspect, the present invention provides a negative electrode additive for a lead-acid battery, comprising the graphene lead oxide powder composite material, wherein the mass percentage of the graphene lead oxide powder composite material in the negative electrode material is 5-10%.

[0016] In a third aspect, the present invention provides a lead-acid battery, comprising the lead-acid battery negative electrode additive.

[0017] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0018] (1) The graphene lead oxide powder composite material of the present invention can be obtained by only one-step reaction. The raw material only needs to be graphite powder, and no expensive graphene is needed. The production process is simple and does not require any intermediate operation, such as washing and drying in water. It can be directly used in production, has low cost, can be mass-produced, and has higher efficiency.

[0019] (2) The gaseous nitrogen dioxide and water released by the decomposition of ammonium nitrate in the present invention increase the interlayer distance in the graphite, thereby synthesizing the graphene lead oxide powder composite material in one step. The metal oxide powder formed in the decomposition process of the present invention is single-phase and has a narrow particle size distribution, and the particle size is mainly concentrated in 0.7-3 μm. The graphene lead oxide powder composite material prepared by the method of the present invention has a carbon content of 18-28%, a purity of 80-90%, a conversion rate of graphite to graphene of 80-90%, and a graphene layer number of 2-3 layers.

[0020] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be achieved and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0022] Figure 1 This is the XRD pattern of the composite material prepared in Example 1 of the present invention;

[0023] Figure 2 This is a particle size distribution diagram of the composite material prepared in Example 1 of the present invention;

[0024] Figure 3 This is a SEM image of the composite material prepared in Example 1 of the present invention;

[0025] Figure 4 This is a BES diagram of the composite material prepared in Example 1 of the present invention;

[0026] Figure 5 This is the Raman spectrum test result of the composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0027] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0028] A specific embodiment of the present invention discloses a method for preparing a graphene lead oxide powder composite material, comprising reacting graphite powder, lead nitrate and ammonium nitrate at a temperature of 400-500°C, for example, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, for 2-4h, for example, 2h, 2.2h, 2.4h, 2.6h, 2.8h, 3.0h, 3.2h, 3.4h, 3.6h, 3.8h, 4h, wherein the gas generated by the reaction is recovered and the solid obtained by the reaction is ground to obtain the graphene lead oxide powder composite material.

[0029] The graphene lead oxide powder composite material of the present invention can be obtained by only one-step reaction, only graphite powder needs to be used as raw material, and expensive graphene does not need to be used. The production process is simple, and no intermediate operation such as washing and drying in water is required. It can be directly used in production, has low cost, can be mass-produced, and has higher efficiency.

[0030] In the present invention, the gaseous nitrogen dioxide and water released by the decomposition of ammonium nitrate increase the interlayer distance in the graphite, thereby synthesizing the graphene lead oxide powder composite material in one step. The metal oxide powder formed during the decomposition process of the present invention is single-phase and has a narrow particle size distribution.

[0031] Specifically, ammonium nitrate is first mixed with graphite powder and lead nitrate to obtain a mixture, the ammonium nitrate is dispersed, the reaction rate is reduced, and the cold mixture is then heated at a high temperature. The material temperature slowly rises above the decomposition temperature and begins to slowly decompose to obtain a graphene lead oxide powder composite material, which will not explode.

[0032] The particle size of the ammonium nitrate in the present invention is 1 to 3 mm.

[0033] In a specific embodiment, the mass ratio of graphite powder, lead nitrate and ammonium nitrate is 0.1-0.4:1:0.3-0.5, for example, 0.1:1:0.3, 0.1:1:0.4, 0.1:1:0.5, 0.2:1:0.3, 0.2:1:0.4, 0.2:1:0.5, 0.3:1:0.3, 0.3:1:0.4, 0.3:1:0.5, 0.4:1:0.3, 0.4:1:0.4, 0.4:1:0.5.

[0034] It should be noted that graphite powder can make the lead oxide generated by the decomposition of lead nitrate more dispersed and loose. Too little graphite powder will cause the lead oxide to agglomerate and clump, and even the appearance of elemental lead; too much graphite powder cannot be fully decomposed, resulting in a large amount of graphite powder residue. Ammonium nitrate is the main material for increasing the distance between graphite layers, and a sufficient content must be ensured; too high a content will accelerate the reaction rate and affect the product morphology, and too much ammonium nitrate will also increase the danger. Therefore, the present invention selects the above ratio.

[0035] The inventors have found through a large number of experiments that the composite material prepared by the reaction temperature, time and raw material ratio of the present invention has a high graphene content, the conversion rate of graphite to graphene can reach 80-90%, and the graphene and lead oxide have a good combination effect.

[0036] It should be noted that the raw materials in the present invention can be in a furnace boat / crucible made of ceramic material, which is convenient for separation of materials after reaction. The furnace boat / crucible can be coated with a glaze that can withstand a temperature of at least 800°C. Preferably, a furnace boat / crucible made of silicon carbide and a carbon binder is used. This is because they have high thermal conductivity, oxidation resistance and chemical reagent tolerance. No need for pre-drying, and can withstand sudden temperature changes when rapidly heated in the furnace and taken out of the furnace. The filling amount of the furnace boat / crucible should not exceed 1 / 3 of the volume. If the furnace boat / crucible is filled to a greater extent during the reaction, the reaction substances may be released into the furnace chamber.

[0037] The preparation method of the present invention can be carried out in a box-type resistance furnace or a continuous belt resistance furnace, and the two can be selected according to actual needs.

[0038] In a specific embodiment, the method further comprises adding an organic swelling agent to carry out the reaction.

[0039] Preferably, the organic swelling agent is ethanol or isopropanol.

[0040] In a specific embodiment, the mass ratio of the organic expander to the graphite powder is 0.05-2:1, for example, 0.05:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1.

[0041] It should be noted that an organic expander can also be added in the present invention. The organic expander releases carbon dioxide and water through pyrolysis, which increases the interlayer distance in the graphite, forms graphene particles, further improves the conversion rate of graphite to graphene, and reduces the number of graphene layers. Since the organic expander is liquid and the rest is solid, adding too much will affect the mixing effect.

[0042] In a specific embodiment, the gas includes nitrogen dioxide.

[0043] In a specific embodiment, the gas is captured and recovered by a wet scrubber, and a saturated sodium hydroxide solution is used as a capture agent in the wet scrubber.

[0044] Specifically, the capture reagent is injected into the wet scrubber through a circulation pump, the waste liquid treated by the wet scrubber is recovered, and the treated gas is clean gas, which is discharged through an exhaust fan.

[0045] In a specific embodiment, the grinding is performed to a particle size of less than 5 microns.

[0046] Another specific embodiment of the present invention discloses a graphene lead oxide powder composite material prepared by the above method.

[0047] In a specific embodiment, the carbon content of the graphene lead oxide powder composite material is 18-28%, for example, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%.

[0048] The purity of the graphene lead oxide powder composite material prepared by the method of the present invention is 80-90%, for example, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, and the conversion rate of graphite to graphene is 80-90%, for example, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%.

[0049] Another specific embodiment of the present invention discloses a lead-acid battery negative electrode additive, comprising the above-mentioned graphene lead oxide powder composite material.

[0050] Specifically, the mass percentage of the additive in the negative electrode material is 5-10%, for example, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%.

[0051] The technical solution of the present invention is further explained below in conjunction with specific embodiments.

[0052] Example 1

[0053] A preparation method of a graphene lead oxide powder composite material of the present embodiment comprises the following steps: mixing graphite powder, lead nitrate and ammonium nitrate in a mass ratio of 0.1:1:0.5, reacting at a temperature of 400°C for 4 hours, wherein the gas generated during the reaction is captured by a wet scrubber, a saturated sodium hydroxide solution is used as a capture reagent in the wet scrubber, the capture reagent is injected into the wet scrubber through a circulation pump, the waste liquid treated by the wet scrubber is recovered, the treated gas is clean gas, and is discharged through an exhaust fan, and the solid obtained by the reaction is ground to a particle size of less than 5 microns to obtain the graphene lead oxide powder composite material.

[0054] The XRD characteristics of the composite material prepared in this embodiment are as follows: Figure 1 As shown, PbO and C are standard spectra. It can be seen from the figure that the XRD spectrum of the composite material only contains peaks of PbO and C, and no other single substances or compounds are detected, indicating that the composite metal oxide prepared in this embodiment is single-phase, only PbO, and does not contain other forms of oxides.

[0055] The particle size distribution of the composite material of this embodiment is as follows Figure 2 As shown, the particle size of the material is mainly concentrated in the range of 0.7-3 μm.

[0056] The SEM images of the composite material of this example are as follows Figure 3 As shown, BES Figure 4 As shown, Figure 3 and 4 The microscopic morphology of the product is shown. It can be seen from the figure that lead oxide and graphene are adhered to each other rather than being independent individuals, which shows that the combination of the two has a good effect.

[0057] Example 2

[0058] A preparation method of a graphene lead oxide powder composite material of the present embodiment comprises the following steps: mixing graphite powder, lead nitrate and ammonium nitrate in a mass ratio of 0.25:1:0.4, reacting at a temperature of 450°C for 3 hours, wherein the gas generated during the reaction is captured by a wet scrubber, a saturated sodium hydroxide solution is used as a capture reagent in the wet scrubber, the capture reagent is injected into the wet scrubber through a circulation pump, the waste liquid treated by the wet scrubber is recovered, the treated gas is clean gas, and is discharged through an exhaust fan, and the solid obtained by the reaction is ground to a particle size of less than 5 microns to obtain the graphene lead oxide powder composite material.

[0059] The graphene lead oxide powder composite material prepared in this example was subjected to the same test as in Example 1, and the results were basically consistent. Due to limited space, they are not listed one by one.

[0060] Example 3

[0061] A preparation method of a graphene lead oxide powder composite material of the present embodiment comprises the following steps: mixing graphite powder, lead nitrate and ammonium nitrate in a mass ratio of 0.4:1:0.3, reacting at a temperature of 500° C. for 2 hours, wherein the gas generated during the reaction is captured by a wet scrubber, a saturated sodium hydroxide solution is used as a capture reagent in the wet scrubber, the capture reagent is injected into the wet scrubber through a circulation pump, the waste liquid treated by the wet scrubber is recovered, the treated gas is clean gas, and is discharged through an exhaust fan, and the solid obtained by the reaction is ground to a particle size of less than 5 microns to obtain the graphene lead oxide powder composite material.

[0062] The graphene lead oxide powder composite material prepared in this example was subjected to the same test as in Example 1, and the results were basically consistent. Due to limited space, they are not listed one by one.

[0063] Example 4

[0064] The graphene lead oxide powder composite material of this embodiment is the same as that of Embodiment 2, except that ethanol is further added to the reaction raw materials, and the mass ratio of the ethanol to the graphite powder is 0.1:1.

[0065] The graphene lead oxide powder composite material prepared in this example was subjected to the same test as in Example 1, and the results were basically consistent. Due to limited space, they are not listed one by one.

[0066] Example 5

[0067] The graphene lead oxide powder composite material of this embodiment is the same as that of Embodiment 2, except that isopropanol is also added to the reaction raw materials, and the mass ratio of isopropanol to graphite powder is 0.2:1.

[0068] The graphene lead oxide powder composite material prepared in this example was subjected to the same test as in Example 1, and the results were basically consistent. Due to limited space, they are not listed one by one.

[0069] Example 6

[0070] The graphene lead oxide powder composite material of this embodiment is the same as that of Embodiment 2, except that ethanol is further added to the reaction raw materials, and the mass ratio of the ethanol to the graphite powder is 0.05:1.

[0071] The graphene lead oxide powder composite material prepared in this example was subjected to the same test as in Example 1, and the results were basically consistent. Due to limited space, they are not listed one by one.

[0072] Comparative Example 1

[0073] The graphene lead oxide powder composite material of this embodiment is the same as that of Embodiment 2, except that the reaction temperature is 380°C.

[0074] Comparative Example 2

[0075] The graphene lead oxide powder composite material of this embodiment is the same as that of Embodiment 2, except that the reaction temperature is 510°C.

[0076] Comparative Example 3

[0077] The graphene lead oxide powder composite material of this embodiment is the same as that of Embodiment 2, except that the reaction time is 1.8 h.

[0078] Comparative Example 4

[0079] The graphene lead oxide powder composite material of this embodiment is the same as that of Embodiment 2, except that the reaction time is 4.2 h.

[0080] Comparative Example 5

[0081] The graphene lead oxide powder composite material of this embodiment is the same as that of Embodiment 2, except that the mass ratio of graphite powder, lead nitrate and ammonium nitrate is 0.5:1:0.3.

[0082] Comparative Example 6

[0083] The graphene lead oxide powder composite material of this embodiment is the same as that of Embodiment 2, except that the mass ratio of graphite powder, lead nitrate and ammonium nitrate is 0.25:1:0.6.

[0084] Test Example 1

[0085] The carbon content, purity and conversion rate of graphite to graphene in the composite materials prepared in Examples 1-6 and Comparative Examples 1-6 were tested respectively. The results are shown in Table 1.

[0086] (1) Test method for conversion rate of graphite to graphene:

[0087] The content of graphene in a mixture of graphite and graphene is not easy to measure directly. In the present invention, the conversion rate of graphene is indirectly tested by the change in specific surface area. The specific surface area of ​​graphene is dozens or even hundreds of times that of graphite. After graphite is converted into graphene, the specific surface area increases sharply. Since only four substances, graphite, graphene, lead oxide, and lead, may exist in the product, the following method steps are used for testing:

[0088] 1) Weigh a certain mass of the product to be tested, place it in a mixed solution of acetic acid + hydrogen peroxide (volume ratio 3:1), and stir to completely dissolve the lead oxide and lead;

[0089] 2) filtering with quantitative filter paper, washing the filter residue with distilled water, and drying the water to obtain a mixture of graphite and graphene;

[0090] 3) Use a specific surface area tester to measure the specific surface area of ​​the mixture, recorded as S1, unit m 2 / g;

[0091] 4) Use a specific surface area tester to measure the specific surface area of ​​raw material graphite, recorded as S2, unit m 2 / g;

[0092] 5) The theoretical specific surface area of ​​graphene in the product is recorded as S3, unit: m 2 / g;

[0093] 6) Assuming that the graphene content is X, the graphite content is 1-X, from which the following equation can be obtained:

[0094] S3·X+S2·(1-X)=S1

[0095] After sorting, the calculation formula of graphene content is:

[0096] X=(S1-S2) / (S3-S2)

[0097] The specific surface area of ​​a single layer of graphene is 2630m 2 / g. Most of the graphene in this product is tested to be 2-3 layers, so the theoretical specific surface area S3 of the graphene in the product is 1052m 2 / g is used to calculate the graphene content and conversion rate in the product.

[0098] (2) Graphene layer number detection method:

[0099] The Raman spectrum of the product was tested using a Renishaw INVIA0820-04 confocal Raman scattering spectrometer, and the product type and number of graphene layers were determined by the position and intensity of the characteristic peaks.

[0100] Figure 5 The Raman spectrum test results of the composite material prepared in Example 1 are shown. The peak G is significantly higher than the D line, indicating that the graphene is of good quality and has a small number of defects. The presence of the 2D peak on the Raman spectrum indicates that the material being tested is graphene. Because the D+D" and D+D' lines detected near the 2D peak are caused by a two-phonon resonance process (single-layer graphene is impossible), this indicates that certain layers of graphene have been formed. According to the intensity ratio of the 2D and G peaks I2D / IG equal to 0.61, it can be concluded that the material at this test point is two-layer graphene. The products obtained in other embodiments or comparative examples were also tested in the same way.

[0101] Table 1

[0102]

[0103] Compared with Example 2, adding an appropriate amount of ethanol or isopropanol organic expanding agent in Examples 4-6 can increase the interlayer distance in graphite, improve the conversion rate of graphite to graphene, reduce the number of graphene layers, and improve the purity of the graphene lead oxide powder composite material to a certain extent.

[0104] Compared with Example 2, the graphene lead oxide powder composite material prepared under the reaction conditions not of the present invention has low purity, low conversion rate of graphite to graphene, and thick graphene layers.

[0105] Compared with Example 2, the graphene lead oxide powder composite materials prepared in Comparative Examples 3-4 not within the reaction temperature of the present invention have low purity, low conversion rate of graphite to graphene, and slightly thick graphene layers.

[0106] Compared with Example 2, the graphene lead oxide powder composite materials prepared in Comparative Examples 5-6 not under the raw material ratio of the present invention have low purity, low conversion rate of graphite to graphene, and thick graphene layers.

[0107] Test Example 2

[0108] The composite materials prepared in Examples 1-6 and Comparative Examples 1-6 were used as additives for the negative electrode of lead-acid batteries, respectively. According to different addition ratios, four addition ratios of 0%, 5%, 10%, and 20% were specifically adopted. The composite material was calculated as the weight of the lead powder, that is, the total weight of the composite material and the lead powder was used as the base. In addition, 0.06% of short fiber, 1% of barium sulfate, 0.3% of humic acid, 0.5% of acetylene black, 0.25% of lignin, 10.15% of pure water, and a density of 1.4 g / cm were added. 3Sulfuric acid 8%, respectively added to the paste machine to mix, to make negative lead paste. The positive electrode also takes the lead powder weight as the base, and adds short fiber 0.1%, stannous sulfate 0.1%, antimony trioxide 0.2%, bismuth trioxide 0.1%, and red lead 5%, respectively added to the paste machine to mix, to make positive lead paste. The rest are made using the same production process, and are made into 2V12Ah single-cell experimental batteries, and the 2hr capacity and cycle life of the batteries are tested. The specific test standards are as follows, and the test results are shown in Table 2.

[0109] 2hr capacity: tested in accordance with GB / T 22199-2017;

[0110] Cycle life: Tested in accordance with GB / T 22199-2017.

[0111] Table 2

[0112]

[0113]

[0114] Compared with Example 2, adding ethanol or isopropanol to the raw materials in Examples 4-6 can increase the 2 hr capacity and cycle life of the battery. This is because the release of carbon dioxide and water through the pyrolysis of the organic expander will increase the interlayer distance in the graphite, forming graphene particles, further increasing the conversion rate of graphite to graphene, thereby improving the battery performance.

[0115] Compared with Example 2 and Comparative Examples 1-2, the 2 hr capacity of the battery made of the graphene lead oxide powder composite material not prepared under the reaction conditions of the present invention does not change much, but the cycle life is significantly reduced.

[0116] Compared with Example 2, in Comparative Examples 3-4, the 2 hr capacity of the battery made of the graphene lead oxide powder composite material not prepared within the reaction time of the present invention does not change much, but the cycle life is significantly reduced.

[0117] Compared with Example 2, the 2 hr capacity of the battery made of the graphene lead oxide powder composite material prepared not under the raw material ratio of the present invention does not change much, the cycle life of Comparative Example 5 is significantly reduced, and the cycle life of Comparative Example 6 is slightly reduced, but the cost of Comparative Example 6 is higher.

[0118] The method of the present invention uses lead nitrate, ammonium nitrate and graphite to prepare a graphene lead oxide powder composite material, and does not require expensive graphene materials to obtain a graphene-rich composite material product, which greatly reduces the production cost. The graphene lead oxide powder composite material prepared by the method of the present invention is mainly used as a negative electrode formula additive for lead-acid batteries, which can significantly improve the capacity and cycle life of the battery.

[0119] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing a graphene lead oxide powder composite material, characterized in that: The method comprises reacting graphite powder, lead nitrate and ammonium nitrate at a temperature of 400-500° C. for 2-4 hours, wherein the gas generated by the reaction is recovered and processed, and the solid obtained by the reaction is ground to obtain the graphene lead oxide powder composite material.

2. The method for preparing a graphene lead oxide powder composite material according to claim 1, characterized in that: The mass ratio of graphite powder, lead nitrate and ammonium nitrate is 0.1-0.4:1:0.3-0.

5.

3. The method for preparing a graphene lead oxide powder composite material according to claim 1 or 2, characterized in that: The method also includes adding an organic swelling agent to carry out the reaction.

4. The method for preparing a graphene lead oxide powder composite material according to claim 3, characterized in that: The organic swelling agent is ethanol or isopropanol.

5. The method for preparing a graphene lead oxide powder composite material according to claim 3, characterized in that: The mass ratio of the organic expander to the graphite powder is 0.05-2:

1.

6. The method for preparing a graphene lead oxide powder composite material according to claim 1, characterized in that: The gas includes nitrogen dioxide.

7. The method for preparing a graphene lead oxide powder composite material according to claim 1, characterized in that: The grinding is performed to a particle size of less than 5 microns.

8. A graphene lead oxide powder composite material prepared by the method according to any one of claims 1 to 7, characterized in that: The carbon content of the graphene lead oxide powder composite material is 18-28%, the purity is 80-90%, and the conversion rate of graphite to graphene is 80-90%.

9. A lead-acid battery negative electrode additive, characterized in that: The invention comprises the graphene lead oxide powder composite material as claimed in claim 8, wherein the mass percentage of the graphene lead oxide powder composite material in the negative electrode material is 5-10%.

10. A lead-acid battery, characterized in that: The lead-acid battery negative electrode additive according to claim 9 is included.

Citation Information

Patent Citations

  • Lead-carbon battery negative plate containing lead and graphene composite materials

    CN102881866A

  • Lead-graphene negative electrode lead paste and preparation method thereof

    CN117174900A

Cited By

  • Nitrogen-doped graphene composite material and preparation method thereof

    CN120964784A